Preparing Primary Education Teachers to Teach Civic Education in the Indonesian Elementary Schools - Yayuk Hidayah (STAI Hubbulwathan Duri, 2023)
The function of education in fostering civic pedagogical skills is important. In particular, this study aims to analyse the function of the elementary education department in fostering the pedagogical skills of primary teachers’ candidates to teach civic education to young learners. As an attempt to collect the data, interviews, observation, documentation, and literature study were employed. The study results indicate that education's function in fostering civic pedagogical skills was conducted through Elementary Civics Education Learning Materials, namely 1) SD PPKn learning methods, 2) Elementary Civic Education materials, and 3) PGSD students’ understanding of the concept of Elementary Civics Education Materials. The recommendation of this research is to make the subject matter Primary PPKn learning as a strategy for increasing the meaning of Citizenship Education in Higher Education.